Engineering hydrogel-based biomedical photonics: design, fabrication, and applications - Guimarães, Carlos F. (2021)
Light guiding and manipulation in photonics have become ubiquitous in events ranging from everyday communications to complex robotics and nanomedicine. The speed and sensitivity of lightâ matter interactions offer unprecedented advantages in biomedical optics, data transmission, photomedicine, and detection of multi-scale phenomena. Recently, hydrogels have emerged as a promising candidate for interfacing photonics and bioengineering by combining their light-guiding properties with live tissue compatibility in optical, chemical, physiological, and mechanical dimensions. Herein, the latest progress over hydrogel photonics and its applications in guidance and manipulation of light is reviewed. Physics of guiding light through hydrogels and living tissues, and existing technical challenges in translating these tools into biomedical settings are discussed. A comprehensive and thorough overview of materials, fabrication protocols, and design architectures used in hydrogel photonics is provided. Finally, recent examples of applying structures such as hydrogel optical fibers, living photonic constructs, and their use as light-driven hydrogel robots, photomedicine tools, and organ-on-a-chip models are described. By providing a critical and selective evaluation of the fieldâ s status, this work sets a foundation for the next generation of hydrogel photonic research.